Assessment of knowledge, attitude and practice of medical students in a Metropolitan city on the role of planetary health in medicine and the impact of climate change on health through a survey - Arun Bharadwaj, Pranav; Jannavada, Hasitha (International Journal Of Community Medicine And Public Health, 2023)
Background: The study identifies medical students as channels of behavior change communication and intends to study the knowledge, attitude and practices of medical students with regard to climate change and its impact on health. The study also aims to address the role of planetary health in medicine. Methods: A questionnaire adapted from the standard KAP Form published by the UNICEF, aimed at assessing the subjects’ knowledge of the effects of climate change on health, their attitude with regard to the present situation, and their involvement in climate friendly activities, was administered upon informed consent. Further, they were enquired about the position of their institution on sustainable practices and climate education. The above was studied through several open and closed ended questions. The data was assessed through relevant tools. Results: The study showed that 94.02% of the subjects believed that climate change was real and 47.87% of them believe that climate change is equally caused by human and environmental factors while 45.30% of them felt human factors were the primary cause of climate change. Nearly 66.68% of the responders considered planetary health and climate change education highly essential components of the medical curriculum. Conclusions: Climate change is a serious concern, and has a severe impact on ecosystems and human health. Medical students must be aware of the role that climate change plays in disease pathophysiology, and act as agents of dissemination of climate education and planetary health.